2006
DOI: 10.1007/s10532-005-4219-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Bioaugmentation on Metal Cyanide Degradation and Soil Bacteria Community Structure

Abstract: Metal cyanides are significant contaminants of many soils found at the site of former industrial activity. In this study we isolated bacteria capable of degrading ferric ferrocyanide and K2Ni(CN)4. One of these bacteria a Rhodococcus spp. was subsequently used to bioaugment a minimal medium broth, spiked with K2Ni(CN)4, containing 1 g of either an uncontaminated topsoil or a former coke works site soil. Degradation of the K2Ni(CN)4 was observed in both soils, however, bioaugmentation did not significantly impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Especially when P. fluorescens was applied, dicyanoaurate does not remain stable in solution with prolonged incubation times. This was already observed in earlier investigations (Brandl et al, 2003) and might by due to sorption processes onto biomass or biodegradation because metal cyanides serve as carbon or nitrogen source (Baxter & Cummings, 2006;Patil & Paknikar, 1999). C. violaceum proved to be more efficient regarding gold mobilization, i.e.…”
Section: Resultssupporting
confidence: 64%
“…Especially when P. fluorescens was applied, dicyanoaurate does not remain stable in solution with prolonged incubation times. This was already observed in earlier investigations (Brandl et al, 2003) and might by due to sorption processes onto biomass or biodegradation because metal cyanides serve as carbon or nitrogen source (Baxter & Cummings, 2006;Patil & Paknikar, 1999). C. violaceum proved to be more efficient regarding gold mobilization, i.e.…”
Section: Resultssupporting
confidence: 64%
“…The annealing temperature for both rounds was 55°C. In order to amplify the total bacterial community, the V3FC and V3R primers were used as described by Baxter and Cummings (2). DGGE.…”
Section: Methodsmentioning
confidence: 99%
“…DGGE. DGGE was carried out using the D-Code system (Bio-Rad Laboratories) as described by Baxter and Cummings (2). Gels were electrophoresed at a current of 200 V for 6 h (nifH) or 200 V for 4.5 h (16S rRNA) at a constant temperature of 60°C.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been reported that some of these methods require high input costs and sophisticated knowledge and/or training to implement successful strategies for their reduction [4]. Meanwhile, scientists have embarked on intense research and simplify reduction methods for these toxicants in the environment by using techniques which are considered environmentally benign, as such novel ways of reducing both cyanogen and mycotoxin levels in the environment, including in agricultural produce destined for consumption, are generally considered cost efective when compared with long-term outcomes of none implementation of control measures [22][23][24].…”
Section: Cyanogen and Mycotoxin Reductionmentioning
confidence: 99%
“…Cyanogens are characterised by the presence of two elements: a carbon: nitrogen functional group held together by a triple bond (─C≡N). The simplest form, which is predominant in the environment, is hydrogen cyanide (HCN), with nitriles and cyanogenic glycosides (CGs) being other forms of these compounds [2][3][4][5]. Generally, free cyanide originates from both anthropogenic and natural processes [6].…”
Section: Introductionmentioning
confidence: 99%